A Macroeconomic Growth Model of Competing Regions - Walter Buhr (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2000)
In the growth context, this paper concentrates on the supply-demand determination of regional equilibrium incomes in regional goods markets as a framework for discussing the implications of competition among regions. Prices at the regional and national level are fixed so that all variables are of real magnitudes; there are no money markets. Regional factor stocks (private and public capital, labor force in the form of human capital) and regional demand set up the barriers to economic growth (cf. generally Barro, Sala-i-Martin (1995)). The analysis is restricted to two regions embedded in the State. The supply side of the model is represented by different regional production function is which generate regional factor demand. Demand-side determination of equilibrium regional incomes arises from the definitions of national accounting enriched by basic behavioral relationships. Substantial consideration is given to the equalization of regional supply and demand in diverging cases (e.g., excess demand in one of the two regions). Changes in factor stocks (differential equations) maintain the dynamics of the model. Regional competition is expressed by variations of regional and state parameters. Their numerical influences on growth will be dealt with in Bobzin (2000).
Keywords: 330